Shear bond strength of resin cement bonded to alumina ceramic after treatment by aluminum oxide sandblasting or silica coating - Passos, Sheila Pestana [UNESP]; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP]; Santos, Maria Jacinta Moraes Coelho; Santos Jr., Gildo Coelho (Wiley, 2011)
Purpose: To evaluate the shear bond strength and bond durability between a dual-cured resin cement (RC) and a high alumina ceramic (In-Ceram Alumina), subjected to two surface treatments. Materials and Methods: Forty disc-shaped specimens (sp) (4-mm diameter, 5-mm thick) were fabricated from In-Ceram Alumina and divided into two groups (n = 20) in accordance with surface treatment: (1) sandblasting by aluminum oxide particles (50 μm Al 2O 3) (SB) and (2) silica coating (30 μm SiO x) using the CoJet system (SC). After the 40 sp were bonded to the dual-cured RC, they were stored in distilled water at 37°C for 24 hours. After this period, the sp from each group were divided into two conditions of storage (n = 10): (a) 24 h-shear bond test 24 hours after cementation; (b) Aging-thermocycling (TC) (12,000 times, 5 to 55°C) and water storage (150 days). The shear test was performed in a universal test machine (1 mm/min). Results: ANOVA and Tukey (5%) tests noted no statistically significant difference in the bond strength values between the two surface treatments (p= 0.7897). The bond strengths (MPa) for both surface treatments reduced significantly after aging (SB-24: 8.2 ± 4.6; SB-Aging: 3.7 ± 2.5; SC-24: 8.6 ± 2.2; SC-Aging: 3.5 ± 3.1). Conclusion: Surface conditioning using airborne particle abrasion with either 50 μm alumina or 30 μm silica particles exhibited similar bond strength values and decreased after long-term TC and water storage for both methods. © 2011 by The American College of Prosthodontists.
Keywords: Alumina; Ceramic; Durability; Shear bond strength; Surface treatments; aluminum oxide; biomaterial; In Ceram Alumina; In-Ceram Alumina; resin cement; silicon dioxide; dental bonding; dental procedure; dental surgery; heat; hydrolysis; materials testing; shear strength; surface property; tooth prosthesis; Air Abrasion, Dental; Aluminum Oxide; Coated Materials, Biocompatible; Dental Bonding; Dental Porcelain; Dental Stress Analysis; Hot Temperature; Hydrolysis; Materials Testing; Resin Cements; Shear Strength; Silicon Dioxide; Surface Properties